(untitled) (Economia Aplicada, 2000)
This paper presents an exercise on comparative efficiency evaluation ofBrazilian federal university hospitals HUs (43 organizations). The methodology used is Data Envelopment Analysis - DEA, along with statistical non-parametric procedures and specific tests. As direct extensions of DEA, the paper also explores the recommended adjustment of inefficient cases to the efficiency frontier, the problem of returns to scale, and the relationships between (in) efficiencies and possible interactions among the HUs. Also, the paper tries to motivate the assessment ofDEA as part of a mechanism of comparative evaluation of complex organizations. Firstly, because DEA identifies "best practices" within the observed cases. Secondly, because DEA can assist public policies, as a useful learning, incentive and coordination instrument.